Untargeted metabolomic profiling of fresh and dried leaf extracts of young and mature Eucalyptus globulus trees indicates differences in the presence of specialized metabolites - Pinto, Mafalda; Soares, Cristiano; Pereira, Ruth; Rodrigues, José António; Fidalgo, Fernanda; Valente, Inês Maria (Frontiers in Plant Science, 2022)
Aqueous extracts from Eucalyptus globulus leaves contain a wide variety of specialized metabolites, mainly polyphenols and appreciable amounts of volatile compounds, which are responsible for their diverse biological activities, such as antioxidant, antimicrobial, and allelopathic features. For this reason, several studies have been conducted to explore the composition of E. globulus leaf extracts for multiple therapeutic and commercial applications. However, so far, the available bibliographic reports only refer to the chemical composition of extracts prepared with leaves from mature trees, leaving much to clarify about the composition of juvenile eucalyptus leaf extracts. Furthermore, there is no consensus regarding the type of leaves, fresh or dried ones, to be used in the extraction procedure, considering the highest recovery of biologically active compounds. In this sense, this study aimed to characterize the chemical composition of aqueous extracts prepared with fresh and dried leaves from young and mature E. globulus trees. For this, leaf biomass from young and mature E. globulus trees was collected in three distinct places from a forest area, and after oven-drying a portion of the leaves, an extraction in hot water was carried out, followed by GC-MS and HPLC-MS/MS analyses. The results revealed that the maturity of eucalyptus trees and biomass drying significantly influenced the volatile and non-volatile composition of the aqueous extracts. Accordingly, while fresh leaf extracts of young trees had great levels of hydrolysable tannins, extracts prepared with fresh leaves from mature trees presented a wide range of terpenes. When dried leaf material was used, extracts had notorious contents of amino acids derivatives, C13 norisoprenoids, fatty and other organic acids. Overall, this study showed, for the first time, that plant maturity (young vs mature) and pre-processing (fresh vs dried) of foliar biomass of E. globulus trees need to be considered in the preparation of leaf aqueous extracts depending on the desired purposes, since major changes in what regards biologically active compounds were found.